An exact exponential time algorithm for counting bipartite cliques - Kutzkov, Konstantin (Information processing letters, 2012)
We present a simple exact algorithm for counting bicliques of given size in a bipartite graph on n vertices. We achieve running time of O(1.2491n), improving upon known exact algorithms for finding and counting bipartite cliques. ► Exact exponential time algorithm for counting bipartite cliques. ► A new simplification rule for handling degree-1 vertices. ► Measure & Conquer analysis.